Reflections on biosafety in the context of COVID-19: repercussions for professionals and for the population (Research, Society and Development, 2020)
Objective: Reflect on the impacts of adopting biosafety measures, both in work spaces and in home settings, resulting from the need to protect against the COVID-19 pandemic. Methodology: This is a reflection study supported by two thematic axes for discussion: biosafety in nursing work to cope with COVID-19 and biosafety in activities of daily living and at home to protect against COVID-19. Results: The pandemic of COVID-19 culminated with changes in procedures, standards and biosafety routines in the context of nursing work and, at the same time, demanded from society the adoption of new behaviors, as a way of preventing contamination by the disease. Conclusion: With the need to adopt biosafety measures in daily work and in the social sphere, the work of nursing professionals gains notoriety, especially with regard to health education, which emerges as an important strategy to face the pandemic.